2018
DOI: 10.4194/1303-2712-v18_7_04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: M ore than half of the landing (70%) of Red mullet (Mullus barbatus) in Turkey is provided from the Black Sea, which is almost all (96%) with bottom trawls. The effect of demersal trawl codend mesh shape and size on the s electivity of Red mullet in the Black Sea was investigated. Selectivity trials were conducted in August 2014 on a commercial trawl boat with conventional (40D), 36 and 40 mm square mesh (36S and 40S) and turned mesh codends (40T90). Data were collected using the covered codend method with a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Whiting, which is a cold water fish, is generally found deeper than 40-45 m throughout the year, whereas red mullet is more common in shallow water than 30 m (Zengin et al, 2015). Kaykaç et al, (2018) indicates that a 40S trawl codend will contribute to the preservation of the red mullet stocks. These results support the use of square mesh codends for whiting and red mullet in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Whiting, which is a cold water fish, is generally found deeper than 40-45 m throughout the year, whereas red mullet is more common in shallow water than 30 m (Zengin et al, 2015). Kaykaç et al, (2018) indicates that a 40S trawl codend will contribute to the preservation of the red mullet stocks. These results support the use of square mesh codends for whiting and red mullet in the region.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it was reported that L50 values were below the first maturity size as well as the MLS in experiments where the codends were made from PE material, having the same characteristics in terms of codend circumference, mesh size and shape (Tokaç et al, 2004;Özbilgin, Tosunoğlu, Tokaç & Metin, 2011;Kaykaç, Zengin & Tosunoğlu, 2018). Many researchers have reported that the type of material used for manufacturing the codend also affects the selectivity and PA nets have a superior selectivity than PE nets (Akyol, Tosunoğlu & Tokaç, 2000;Deval, Bök, Ateş & Özbilgin, 2006;Tokaç et al, 2004).…”
Section: Discussionmentioning
confidence: 99%